Rural Electrification Using Gram Jyoti Doot, Mobile, And Web-Based Application - Sharma, Bhawna; Sharma, Akshay; Rajput, Akash; Gupta, Parnika; Dhiman, R; Gandotra, Sheetal (International Journal of Computer Sciences and Engineering, 2025)
Pradhan Mantri Sahaj Bijli Har Ghar Yojana’ – Saubhagya is a Government Scheme to achieve 100% household electrification in the country in rural as well as urban areas by 31st March 2019. GramJyotiDoot, developed in collaboration with Jammu and Kashmir Power Development Department (JKPDD)is a well-organized and consistent approach to support Saubhagya. GramJyotiDoot comprises an android application and web-portals for Junior Engineers (JEs) and Assistant Executive Engineers (AEEs). The objective of GramJyotiDoot is to eliminate the cumbersome procedure of filing the documents for obtaining a new electricity connection and making the procedure simple by going digital. This expedites the process of registration of new connections and electrification of unelectrified households. The new connections in the rural areas of Jammu and Kashmir are being released using GramJyotiDoot